Building Indonesia Emas 2045 with Pancasila and Eco-Maqasid Plus for a Just and Sustainable Civilization - Endika, Yepri; Aminy, Muhammad Habibullah; Siswanto, Siswanto (Pancasila: Jurnal Keindonesiaan, 2026)
The vision of Indonesia Emas 2045 is not merely an economic growth target but a civilizational agenda that requires a transformation of development values and ethics. This article aims to formulate a philosophical strategic framework based on the integration of Pancasila values and Eco-Maqasid Plus (+) principles as an ethical foundation for policies toward a just and sustainable future. The research employs a qualitative approach with a descriptive analytical method through a conceptual review. Data analysis was conducted using a hermeneutic philosophical approach across three coherent interpretative stages: ontological, epistemological, and axiological. The findings demonstrate that the integration of Pancasila and Eco-Maqasid+ serves as a tool to deconstruct the failures of materialistic development by offering a Theo-Ecocentrism paradigm. This framework functions as an ethical compass in addressing digital disruption and ecological crises by strengthening digital ethics and fostering an inclusive and sustainable Green Economy. Moreover, the younger generation particularly Gen Z and Gen Alpha, are positioned as key actors in sustaining this civilizational vision through digital ethics, ecological awareness and value-based leadership. As a recommendation, this study proposes the integration of Eco-Maqasid+ parameters into national development performance indicators to ensure that investment policies align with environmental carrying capacity and human dignity. With the spirit of Pancasila and an ecological breath, Indonesia Emas 2045 is expected to evolve into a meaningful, just, civilized, and sustainable civilization.